(untitled) (Bangladesh Journal of Botany, 2022)
Wine grape cannot grow well in cold areas. The cold resistance abilities of grape have become a very important problem to be solved. Effects of different fruit loads on the physiological and biochemical indexes of wine grape cultivar were studied through experiments. Results showed that different fruit loads had significant effects on the conductivity, soluble sugar content, Malondialdehyde (MDA), superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) of grape branches. Factor analysis and principal component analysis were used to analyze the physiological and biochemical indexes of cold resistance of wine grapes with different loads. Results showed that combined with the physical microstructure, physiological and biochemical data of branches, the best fruit load of wine grape was 5 kg in eastern foot of Helan Mountain, China. Bangladesh J. Bot. 51(2): 263-270, 2022 (June)